Bifurcation phase portraits and nonlinear wave solutions for the modified Konopelchenko-Dubrovsky equation - Ming Song; Shenhui Wu (Alexandria Engineering Journal, 2023)
The bifurcation phase portraits and exact nonlinear wave solutions of the modified Konopelchenko-Dubrovsky (KD) equation are studied by using the bifurcation method. The bifurcation phase portraits of the modified KD equation are given when a>0 and a<0. When different combinations of the parameters a, b, k and n, eighteen new exact nonlinear wave solutions for the modified KD equation are obtained.